Role of Physics Student Worksheet in Facilitating the Student’ Scientific Literacy Skills: A Systematic Literature Review - Shabrina Muthia Herman; Pakhrur Razi; Hamdi Hamdi; Selma Riyasni (Jurnal Penelitian Pembelajaran Fisika, 2025)
This study aims to systematically analyze the role of Student Worksheets in facilitating the improvement of students’ scientific skills. Student worksheets serve as an instructional medium that encourages students to engage actively in the process of observation, experimentation, and reasoning to develop scientific literacy. Using a systematic literature review approach, this research examined 15 articles published in SINTA-indexed national journals between 2015 and 2025. The review process involved identifying, selecting, and analyzing articles that focused on the development or implementation of student worksheets to enhance students’ scientific skills. Data were analyzed descriptively and thematically to identify trends, models, and outcomes from previous studies. The findings reveal that most student worksheets were developed using active learning models, such as Problem-Based Learning (PBL), Guided Inquiry, Learning Cycle 5E, STEM, and Ethnoscience, all of which have been proven valid, practical, and effective in improving students’ reasoning, analytical thinking, and inquiry abilities. The integration of digital and contextual elements further supports engagement and aligns with 21st-century learning competencies. Therefore, student worksheets can be regarded as an effective educational tool to strengthen students’ scientific skills and promote inquiry-based learning in various scientific contexts.